Wrongful Discharge Laws and Innovation - Acharya, Viral V.; Baghai, Ramin P.; Subramanian, Krishnamurthy V. (Review of Financial Studies, 2014)
We show that wrongful discharge laws—laws that protect employees against unjust dismissal—spur innovation and new firm creation. Wrongful discharge laws, particularly those that prohibit employers from acting in bad faith ex post, limit employers' ability to hold up innovating employees after the innovation is successful. By reducing the possibility of holdup, these laws enhance employees'innovative efforts and encourage firms to invest in risky but potentially mould-breaking projects. We develop a model and provide supporting empirical evidence of this effect using the staggered adoption of wrongful discharge laws across U.S. states.